GNSS for Vehicle Control. - Bevly, David M. (Artech House, 2010)
As global navigation satellite systems (GNSS) such as GPS have grown more pervasive, the use of GNSS to automatically control ground vehicles has drawn increasing interest. This cutting-edge resource offers you a thorough understanding of this emerging application area of GNSS. Written by highly-regarded authorities in the field, this unique reference covers a wide range of key topics, including ground vehicles models, psuedolites, highway vehicle control, unmanned ground vehicles, farm tractors, and construction equipment. The book is supported with over 150 illustrations and more than 180 eq.